Severe Case of Plasmodium falciparum Malaria in a Pregnant Woman from Nigeria - Kruti Yagnik; Bilal Farooqi; Molly W. Mandernach; Anthony P. Cannella; Gautam Kalyatanda (Case Reports in Infectious Diseases)
Human malaria has arguably affected more of human history than any other pathogen. Pregnant women have a higher risk of developing severe malaria as well as the risk of severe complications. We present a case of severe malaria in a pregnant patient from sub-Saharan Africa who was treated successfully with artesunate. A 28-year-old Nigerian woman with a 20-week intrauterine pregnancy presented with a five-day history of fever and diffuse joint pains. Evaluation of peripheral thin blood smear demonstrated a parasitemia of 9.8%. The patient was admitted to the intensive care unit, and oral clindamycin/quinine was initiated until intravenous artesunate was obtained. The patient completed four doses of IV artesunate, and after the 4th dose of artesunate, no blood parasites were seen on peripheral smear. The patient was discharged home and, upon clinic follow-up, did not have any further complications associated with either her disease or therapy. A review on the treatment of severe malaria in all trimesters of pregnancy supports the WHO recommendation for intravenous artesunate as the drug of choice. This case illustrates the importance of recognizing malaria in pregnant women from endemic countries and shows that artesunate compounds can be used safely in pregnancy, particularly with high parasitemia.